Auxiliary activation aluminum-silicon co-permeation coating and preparation method thereof

By assisted activated aluminum and silicon coating coating method, the problem of poor adhesion and restricted corrosion performance in the surface thermal anticorrosive technology in the boiler pipeline in the boiler pipeline is solved. Boiler pipelines under steam temperature and pressure conditions.

CN119368408APending Publication Date: 2025-01-28HUANENG HUNAN YUEYANG POWER GENERATION CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411286863.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The thermal corrosion protection technology of the existing boiler pipes has problems such as poor coating adhesion and limited corrosion resistance, especially under high steam temperature and pressure conditions, which are difficult to effectively prevent corrosion.

Method used

Adopt the auxiliary activated aluminum silicon co -coating preparation method. After the metal powder is used for ball grinding and mixed with the liquid component to form a slurry layer and is dried, sintering, and electrolytic activation, it will eventually form a dense aluminum silicon silicon silicon silicon High temperature corrosion resistance.

Benefits of technology

The efficient adhesion of aluminum and silicon coatings and excellent anti -high and low temperature corrosion and anti -steam oxidation properties are realized, and the surface hardness, corrosion resistance and wear resistance of the workpiece are improved. At the same time, the preparation process is simplified and the pollution and cost are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119368408A_ABST
    Figure CN119368408A_ABST
Patent Text Reader

Abstract

The invention discloses an activation-assisted aluminum-silicon co-permeation coating and a preparation method thereof, and belongs to the technical field of coatings. The preparation method comprises the following steps: uniformly mixing metal powder, and then carrying out ball milling to obtain a solid-phase component; uniformly mixing the solid-phase component and the liquid-phase component, and coating the surface of a preheated workpiece with the mixture to form a slurry layer; and then drying, curing and sintering are carried out, an aluminum-silicon metal powder high-temperature corrosion-resistant coating is obtained, finally, electrolytic activation treatment is carried out on the coating, and the aluminum-silicon co-permeation coating can be obtained. The method is suitable for various metal parts such as carbon steel, austenitic steel and high-temperature alloy, and the prepared metal powder coating is good in surface quality, high in production efficiency and excellent in corrosion resistance and oxidation resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coatings, and in particular relates to an auxiliary activated aluminum-silicon co-penetration coating and a preparation method thereof. Background Art

[0002] The thermal corrosion protection of the inner surface of boiler pipes has always been one of the factors restricting thermal power generation. Especially at the current stage, the working conditions of thermal power generation are developing towards higher steam temperature and pressure. It is urgent to improve the thermal corrosion protection performance of the inner surface of pipes.

[0003] At present, the most common anti-corrosion technology is the technology of infiltrating corrosion-resistant metals on the alloy surface, such as Al, Si, chromium, etc.; Al film is formed on the alloy surface by infiltrating Al, and the compactness of alumina hinders the corrosion of the substrate by water vapor; Si infiltration improves the corrosion resistance of the substrate itself, and the combination of the two improves the overall corrosion resistance. Due to the surface defects of metal powder coating film, the anti-corrosion performance of the coating is limited. Due to the limitations of the coating preparation process, the adhesion of the coating is often poor, resulting in a limited coating life.

[0004] The electrolytic activation process is a surface activation process based on electrochemical principles. The stainless steel material is immersed in an electrolyte and a voltage is applied to form a dense oxide film on the surface of the material, thereby improving its surface hardness, corrosion resistance, wear resistance and other comprehensive properties. In addition, this process can also eliminate surface microscopic defects and improve its glossiness and flatness. Summary of the invention

[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0006] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0007] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing an auxiliary activated aluminum-silicon co-diffusion coating.

[0008] In order to solve the above technical problems, the present invention provides the following technical solutions, including:

[0009] The metal powders are mixed evenly and then ball-milled to obtain a solid phase component; the solid phase component and the liquid phase component are mixed evenly and applied to the preheated workpiece surface to form a slurry layer; then the mixture is dried, solidified and sintered to obtain an aluminum-silicon metal powder high-temperature corrosion-resistant coating, and finally the coating is electrolytically activated to obtain an aluminum-silicon co-infiltration coating;

[0010] Wherein, the solid-to-liquid ratio of the solid phase component to the liquid phase component is 10:1-5.

[0011] As a preferred scheme for the preparation method of the auxiliary activated aluminum-silicon co-diffusion coating described in the present invention, the solid phase components include, by mass percentage, 50-80% aluminum powder, 0-10% silicon powder, 0-20% aluminum oxide, 0-20% chromium oxide, 1-5% ammonium chloride and 1-5% lanthanum oxide.

[0012] As a preferred embodiment of the method for preparing the auxiliary activated aluminum-silicon co-diffusion coating of the present invention, the ball milling has a rotation speed of 350 to 400 r / min and a ball milling time of 6 to 24 h.

[0013] As a preferred scheme for the preparation method of the auxiliary activated aluminum-silicon co-diffusion coating described in the present invention, the liquid phase components include, by mass percentage, 10-30% of aluminum dihydrogen phosphate, 5-15% of sodium silicate, 10-20% of organic binder and 0-30% of curing agent.

[0014] As a preferred scheme for the preparation method of the assisted activated aluminum-silicon co-diffusion coating described in the present invention, the organic binder includes one or more of polyurethane, nitrocellulose or polyvinyl acetate; the curing agent includes one or more of melamine formaldehyde resin, ethylenediamine, acid anhydride, resol phenolic resin, amino resin, dicyandiamide, meta-phenylenediamine or hydrazide.

[0015] As a preferred embodiment of the method for preparing the auxiliary activated aluminum-silicon co-diffusion coating of the present invention, the preheating temperature is 150-220°C and the time is 30-60 minutes; the thickness of the slurry layer is 0.1-1.0 mm.

[0016] As a preferred scheme for the preparation method of the auxiliary activated aluminum-silicon co-diffusion coating described in the present invention, the drying and curing adopts a segmented gradient curing process, specifically: pre-drying at 50-120°C for 5-30 minutes, then drying at 140-160°C for 30-60 minutes, and finally medium-temperature curing at 250-300°C for 30-60 minutes.

[0017] As a preferred solution of the preparation method of the auxiliary activated aluminum-silicon co-diffusion coating described in the present invention, the sintering temperature is 300-700°C, the time is 5-30 minutes, and the heating rate is 950-1050°C / min.

[0018] As a preferred solution of the method for preparing the auxiliary activated aluminum-silicon co-diffusion coating described in the present invention, the voltage of the electrolytic activation is 4 to 6V, and the activation time is 10 to 30 minutes.

[0019] The purpose of the present invention is to overcome the deficiencies in the prior art and provide an auxiliary activated aluminum-silicon co-penetration coating.

[0020] Beneficial effects of the present invention:

[0021] (1) The metal powder raw material of the present invention is suitable for various metal workpieces whose surfaces need to be strengthened, including carbon steel, austenitic stainless steel, high-temperature alloy and other workpieces, and has a wide range of applications and strong practicality.

[0022] (2) The aluminum silicon high temperature corrosion resistant coating infiltrated with metal powder described in the present invention does not need to be prepared under vacuum conditions, and the preparation process is simple. At the same time, the aluminum silicon infiltration layer has high preparation efficiency, low pollution, adjustable thickness, good wear resistance, and especially excellent resistance to high and low temperature corrosion and steam oxidation.

[0023] (3) After electrolytic activation treatment, a dense oxide film is formed on the surface of the workpiece, thereby improving its comprehensive properties such as surface hardness, corrosion resistance and wear resistance. In addition, this process can also eliminate surface microscopic defects and improve its gloss and flatness. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. Among them:

[0025] Figure 1 It is a process flow chart of an embodiment of the present invention.

[0026] Figure 2 This is a cross-sectional view of the sample coating prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0027] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0028] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0029] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0030] The raw materials used in the present invention are all commercially available unless otherwise specified.

[0031] The steam oxidation resistance of the device was measured by placing the device in a 650°C steam environment for 500 hours and measuring the weight gain.

[0032] Example 1

[0033] This embodiment provides a method for preparing an activated aluminum-silicon co-penetration coating, referring to Figure 1 , specifically:

[0034] 1) Pipeline surface cleaning

[0035] Use alcohol and acetone to clean oil stains and dust on the pipe surface, and use a steel brush to remove surface oxide scale.

[0036] 2) Slurry coating on pipeline surface

[0037] After preheating the pipeline at 220℃ for 30 minutes, apply the slurry to the pipeline surface at one time by spraying. Do not apply it in layers multiple times. The thickness of the coating slurry layer is 0.5mm.

[0038] The preparation method of the metal powder coating raw material is as follows: 60% aluminum powder, 5% silicon powder, 15% aluminum oxide, 10% chromium oxide, 5% ammonium chloride and 5% lanthanum oxide are weighed by mass percentage, mixed evenly and ball milled at a speed of 350r / min for 8h to obtain a solid phase component. 15% aluminum dihydrogen phosphate, 10% sodium silicate, 12% organic binder (polyvinyl acetate) and 20% curing agent (melamine formaldehyde resin) are weighed by mass percentage, deionized water is used as a solvent, and mixed and stirred to obtain a liquid phase component.

[0039] The solid phase component and the liquid phase component are mixed at a solid-liquid ratio (g:ml) of 10:2 to obtain aluminum silicon slurry.

[0040] 3) Drying and curing

[0041] The metal pipe coated with aluminum silicon slurry was pre-dried at 60°C for 5 minutes, then dried at 100°C for 55 minutes, and finally cured at 250°C for 30 minutes.

[0042] 4) Rapid sintering

[0043] The pipeline is rapidly sintered and diffused by aluminum-silicon co-infiltration by rapid heating, and then air-cooled to room temperature; the heating rate is set to 1000°C / min, the holding temperature is 500°C, and the holding time is 30min.

[0044] 5) Electrolytic activation

[0045] The workpiece with aluminum silicon coating is placed in an electrolyte for electrolytic activation treatment. The electrolytic activation voltage is 4V and the activation time is 30min.

[0046] Figure 2 This is a cross-sectional view of the sample coating prepared in Example 1 of the present invention. It can be seen from the figure that the thickness of the diffusion layer is 30-40 μm, the diffusion layer is relatively dense, and the outermost layer is particularly dense, and it is well bonded to the substrate, indicating that the coating prepared by this method is better.

[0047] Example 2

[0048] The difference between this embodiment and embodiment 1 is that the organic binder is adjusted to nitrocellulose, and the rest of the preparation process is the same as that of embodiment 1 to obtain an aluminum-silicon co-penetration coating.

[0049] Example 3

[0050] The difference between this embodiment and embodiment 1 is that the organic binder is adjusted to polyurethane, and the rest of the preparation process is the same as that of embodiment 1 to obtain an aluminum-silicon co-penetration coating.

[0051] The coating prepared in the above embodiment was subjected to a performance test, and the comparison results with those in Example 1 are shown in Table 1.

[0052] Table 1

[0053] Example 1 Example 2 Example 3 Effective coating coverage (%) 98 76 82 Hardness (HV) 586 476 501 <![CDATA[Weight gain (mg / cm 2 ) in a 650 °C steam environment for 500 h 0.0381 0.0403 0.0387

[0054] It can be seen from the above table that adjusting the type of binder has a significant effect on the coating performance, which is due to the different adhesives having different adhesion effects on the pipe wall in the coating preparation method. According to the results in the above table, the best technical effect can be obtained when the binder in the present invention is polyvinyl acetate.

[0055] Example 4

[0056] The difference between this embodiment and embodiment 1 is that the curing agent is adjusted to m-phenylenediamine, and the rest of the preparation process is the same as that of embodiment 1 to obtain an aluminum-silicon co-penetration coating.

[0057] Example 5

[0058] The difference between this embodiment and embodiment 1 is that the curing agent is adjusted to ethylenediamine, and the rest of the preparation process is the same as that of embodiment 1 to obtain an aluminum-silicon co-penetration coating.

[0059] The coating prepared in the above embodiment was subjected to a performance test, and the comparison results with those in Example 1 are shown in Table 2.

[0060] Table 2

[0061] Example 1 Example 4 Example 5 Effective coating coverage (%) 98% 52% 57% Hardness (HV) 586 357 374 <![CDATA[Weight gain (mg / cm 2 ) in a 650°C steam environment for 500 h 0.0381 0.2073 0.1954

[0062] As can be seen from the above table, adjusting the curing agent has a significant effect on the coating performance. This is because different curing agents show large differences in effect during the curing process, which directly affects the penetration of the effective ingredients during the sintering process. According to the results in the above table, the best technical effect can be obtained when the curing agent in the present invention is melamine formaldehyde resin.

[0063] Example 6

[0064] The difference between this embodiment and embodiment 1 is that the aluminum dihydrogen phosphate in the solvent is adjusted to sodium dihydrogen phosphate, and the rest of the preparation process is the same as that of embodiment 1 to obtain an aluminum-silicon co-diffusion coating.

[0065] Example 7

[0066] The difference between this embodiment and embodiment 1 is that the aluminum dihydrogen phosphate in the solvent is adjusted to potassium dihydrogen phosphate, and the rest of the preparation process is the same as that of embodiment 1 to obtain an aluminum-silicon co-diffusion coating.

[0067] The coating prepared in the above embodiment was subjected to a performance test, and the comparison results with those in Example 1 are shown in Table 3.

[0068] Table 3

[0069] Example 1 Example 6 Example 7 Coating aluminum content (%) 25 12 13 Hardness (HV) 586 334 346 <![CDATA[Weight gain (mg / cm 2 ) in a 650°C steam environment for 500 h 0.0381 0.3625 0.3287

[0070] It can be seen from the above table that adjusting the liquid phase solvent composition has a significant effect on the coating performance. This is because aluminum dihydrogen phosphate has its own aluminum source, and in addition, it decomposes and volatilizes P during the sintering process. 2 O 5 , forming a ceramic bond, no low melting point is generated at high temperature, and also plays a role in high temperature bonding of the coating. According to the results in the above table, the best technical effect can be obtained when the aluminum dihydrogen phosphate in the present invention is a liquid phase solvent.

[0071] Example 8

[0072] The difference between this embodiment and embodiment 1 is that the pre-drying temperature is adjusted to 50° C., and the rest of the preparation process is the same as that of embodiment 1 to obtain an aluminum-silicon co-diffusion coating.

[0073] Example 9

[0074] The difference between this embodiment and embodiment 1 is that the pre-drying temperature is adjusted to 120° C., and the rest of the preparation process is the same as that of embodiment 1 to obtain an aluminum-silicon co-diffusion coating.

[0075] The coating prepared in the above embodiment was subjected to a performance test, and the comparison results with those in Example 1 are shown in Table 4.

[0076] Table 4

[0077] Example 1 Example 8 Example 9 Effective coating coverage (%) 98 75 77 Hardness (HV) 586 459 483 <![CDATA[Weight gain (mg / cm) in a 650 °C steam environment for 500 h 2 )]]> 0.0381 0.0694 0.0639

[0078] As can be seen from the table above, adjusting the pre-drying temperature has a significant effect on the coating performance. This is because the pre-drying temperature directly affects the surface state of the slurry before sintering. When the temperature is too high, the coating layer is prone to cracks, and when the temperature is too low, the coating layer cannot be evenly attached to the substrate surface. According to the results in the table above, the best technical effect can be obtained when the estimated drying temperature in the present invention is 75-85°C.

[0079] Example 10

[0080] The difference between this embodiment and embodiment 1 is that the sintering temperature is adjusted to 300° C., and the rest of the preparation process is the same as that of embodiment 1 to obtain an aluminum-silicon co-diffusion coating.

[0081] Embodiment 11

[0082] The difference between this embodiment and embodiment 1 is that the sintering temperature is adjusted to 700° C., and the rest of the preparation process is the same as that of embodiment 1 to obtain an aluminum-silicon co-diffusion coating.

[0083] The coating prepared in the above embodiment was subjected to a performance test, and the comparison results with those in Example 1 are shown in Table 5.

[0084] Table 5

[0085] Example 1 Example 10 Embodiment 11 Coating aluminum content (%) 25 8 12 Hardness (HV) 586 328 387 <![CDATA[Weight gain (mg / cm 2 ) in a 650°C steam environment for 500 h 0.0381 0.6839 0.5386

[0086] As can be seen from the table above, adjusting the sintering temperature has a significant effect on the coating performance, because the sintering temperature directly affects the diffusion rate of effective elements, and the sintering temperature also directly affects the stability of the coating. According to the results in the table above, the best technical effect can be obtained when the sintering temperature in the present invention is 500°C.

[0087] Example 12

[0088] The difference between this embodiment and embodiment 1 is that the voltage of electrolytic activation is adjusted to 2V, and the rest of the preparation process is the same as that of embodiment 1 to obtain an aluminum-silicon co-diffusion coating.

[0089] Embodiment 13

[0090] The difference between this embodiment and embodiment 1 is that the voltage of electrolytic activation is adjusted to 6V, and the rest of the preparation process is the same as that of embodiment 1 to obtain an aluminum-silicon co-diffusion coating.

[0091] Embodiment 14

[0092] The difference between this embodiment and embodiment 1 is that the activation time of electrolysis is adjusted to 10 minutes, and the rest of the preparation process is the same as that of embodiment 1 to obtain an aluminum-silicon co-diffusion coating.

[0093] Embodiment 15

[0094] The difference between this embodiment and embodiment 1 is that the activation time of electrolysis is adjusted to 60 minutes, and the rest of the preparation process is the same as that of embodiment 1 to obtain an aluminum-silicon co-diffusion coating.

[0095] The coating prepared in the above embodiment was subjected to performance testing, and the results compared with those in Example 1 are shown in Table 6.

[0096] Table 6

[0097]

[0098] It can be seen from the above table that the electrolytic activation process parameters have a great influence on the coating. Reducing the electrolytic voltage or shortening the electrolytic time can easily lead to insufficient electrolytic activation, while increasing the electrolytic voltage or extending the electrolytic time can easily lead to surface burning, both of which have a great impact on the quality of the coating.

[0099] Comparative Example 1

[0100] The difference between this comparative example and Example 1 is that the electrolytic activation process is removed, and the remaining preparation processes are the same as those in Example 1 to obtain an aluminum-silicon co-diffusion coating.

[0101] The coating prepared in the above comparative example was subjected to performance testing, and the comparison results with those of Example 1 are shown in Table 7.

[0102] Table 7

[0103] Example 1 Comparative Example 1 Coating porosity (%) 0.01 5 Hardness (HV) 586 308 <![CDATA[Weight gain (mg / cm) in a 650 °C steam environment for 500 h 2 )]]> 0.0381 0.3531

[0104] It can be seen from the above table that the electrolytic activation process has a fundamental effect on improving the coating quality. This is because the electrolytic activation directly affects the surface state and affects the pore formation of the coating.

[0105] In summary, the metal powder raw material used in the present invention is suitable for various metal workpieces whose surfaces need to be strengthened, including carbon steel, austenitic stainless steel, high-temperature alloy and other workpieces, and has a wide range of applications and strong practicality.

[0106] The aluminum-silicon high-temperature corrosion-resistant coating and its preparation method do not need to be carried out under vacuum conditions, and the preparation process is simple. At the same time, the aluminum-silicon diffusion layer has high preparation efficiency, low pollution, adjustable thickness, good wear resistance, and especially excellent resistance to high and low temperature corrosion and steam oxidation.

[0107] After electrolytic activation treatment, a dense oxide film is formed on the surface of the workpiece, thereby improving its comprehensive properties such as surface hardness, corrosion resistance and wear resistance. In addition, this process can also eliminate surface microscopic defects and improve its glossiness and flatness.

[0108] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A method for preparing an activated aluminum-silicon co-penetration coating, characterized in that: include, The metal powders are mixed evenly and then ball-milled to obtain a solid phase component; the solid phase component and the liquid phase component are mixed evenly and applied to the preheated workpiece surface to form a slurry layer; then the mixture is dried, solidified and sintered to obtain an aluminum-silicon metal powder high-temperature corrosion-resistant coating, and finally the coating is electrolytically activated to obtain an aluminum-silicon co-infiltration coating; The solid-liquid ratio of the solid phase component to the liquid phase component is 10:1-5; the voltage of the electrolytic activation is 4-6V, and the activation time is 10-30min.

2. The method for preparing the activated aluminum-silicon co-penetration coating according to claim 1, characterized in that: In terms of mass percentage, the solid phase components include 50-80% aluminum powder, 0-10% silicon powder, 0-20% aluminum oxide, 0-20% chromium oxide, 1-5% ammonium chloride and 1-5% lanthanum oxide.

3. The method for preparing the activated aluminum-silicon co-penetration coating according to claim 1, characterized in that: The ball milling process has a rotation speed of 350 to 400 r / min and a ball milling time of 6 to 24 h.

4. The method for preparing the activated aluminum-silicon co-penetration coating according to claim 1, characterized in that: In terms of mass percentage, the liquid phase components include 10-30% of aluminum dihydrogen phosphate, 5-15% of sodium silicate, 10-20% of an organic binder and 0-30% of a curing agent.

5. The method for preparing the activated aluminum-silicon co-penetration coating according to claim 4, characterized in that: The organic binder includes one or more of polyurethane, nitrocellulose or polyvinyl acetate; the curing agent includes one or more of melamine formaldehyde resin, ethylenediamine, acid anhydride, resol phenolic resin, amino resin, dicyandiamide, metaphenylenediamine or hydrazide.

6. The method for preparing the activated aluminum-silicon co-penetration coating according to claim 1, characterized in that: The preheating temperature is 150-220° C. and the preheating time is 30-60 minutes.

7. The method for preparing the activated aluminum-silicon co-penetration coating according to claim 1, characterized in that: The thickness of the slurry layer is 0.1-1.0 mm.

8. The method for preparing the activated aluminum-silicon co-penetration coating according to claim 1, characterized in that: The drying and curing adopts a segmented gradient curing process, specifically: pre-drying at 50-120°C for 5-30 minutes, then drying at 140-160°C for 30-60 minutes, and finally medium-temperature curing at 250-300°C for 30-60 minutes.

9. The method for preparing the activated aluminum-silicon co-penetration coating according to claim 1, characterized in that: The sintering temperature is 300-700° C., the sintering time is 5-30 minutes, and the heating rate is 950-1050° C. / min.

10. The aluminum-silicon co-penetration coating prepared by the preparation method according to any one of claims 1 to 9.